The interaction of BIM And FM through sport projects life cycle (case study: Sailia training site in Qatar). Issue 1 (31st December 2022) - Omayer, Hayam M.; Selim, Omar
ABSTRACT: 'It is all about the data'. In this context, 'data' refers to the massive amounts of information facility managers require for their work, including the frameworks that serve as the basis for successful and productive facility management (FM). The paper discusses building information modeling (BIM) and how this can be applied to facility management to address current industry challenges to BIM & FM Interaction. The research is dependent on transforming the interaction of more specialization in engineering by linking the different disciplines in a single project and using new technologies in a case study project. This construction project is concerned with the role of BIM and construction operations building information exchange (COBie) in sports facilities and operations and maintenance (O & M) information to view the benefits of BIM-based on the experience of the Arab world in the field of construction. The research presents a case study for the Technical Masterclass, Delivering the BIM/COBie & IFC in Revit according to the NBIMS-US COBie standard to support the facility's management. The project is FIFA training facilities, Sailia Training Site. This case study project examines the role of BIM and COBie in facility and O & M information to demonstrate the benefits of BIM. The idea of BIM for facility management is implemented through COBie as a data transfer method.